Integrated Marketing Communication Strategy for Cosmetic Retail Company: a Study of New Central Palu - Gabriela Liem, Anastasia; Nurlaela Arief, Neneng (Cv. Syntax Corporation Indonesia, 2023)
New Central Palu is non-food modern retail store located in Palu, Central Celebes. It sells wide range of products with cosmetic as the main product. Currently, New Central Palu experiences stagnant sales and lack of awareness. Therefore, this study aims to identify the problems and propose integrated marketing communication strategy to solve the problems. Both quantitative and qualitative methods are used in this research. Thus, data collection is done using in-depth interview to internal management of New Central Palu and questionnaire distribution to the target market. In-depth interview is explored from head of purchasing, head of marketing and sales, and general manager of New Central Palu. Besides, online questionnaire using google form has been distributed to 193 respondents through New Central Palu's official instagram. Secondary data from other resources, such as books, journal, and others is also collected to support the data analysis. Internal analysis is done using STP analysis, marketing mix, and VRIO analysis while external analysis is implemented using PESTEL analysis, porter's five forces, and customer analysis. Then, SWOT analysis is done before integrated marketing communication strategy is proposed. Six marketing communication mix channel is used, including advertising, personal selling, sales promotion, public relation, direct marketing and digital marketing to optimize the resut. It can be concluded that New Central Palu has a enormous business potential as modern retail cosmetic store in Palu. However, there are some marketing strategy and recommendation that should be implemented.